Assessing the Benefit of Polymer‐Coated Urea for Corn Production on Irrigated Sandy Soils. (1st March 2019) - Rui, Yichao; Ruark, Matthew D.; Andraski, Todd W.; Bundy, Larry G.
Abstract : Core Ideas: Polymer‐coated urea led to greater yields compared to other N fertilizers when all applied preplant. The performance of preplant polymer‐coated urea is reduced in high rainfall years. Split application of ammonium sulfate consistently produced the greatest yields on irrigated sands. Nitrification inhibitor showed little impact on corn yield on irrigated sandy soils. Polymer‐coated urea (PCU) is an enhanced‐efficiency fertilizer product that can potentially increase N use efficiency, thereby reducing N losses to the environment. However, the optimum timing and rates of PCU application under varying seasonal precipitation is less known. Here we studied the response of corn ( Zea mays L.) yield and N use efficiency to N timing (preplant, sidedress, and split application) and rates (112–280 kg N ha −1 ) of PCU, ammonium sulfate (AS), and urea, including a control treatment without N, on an irrigated sandy soil (90% sand) in central Wisconsin from 2003 to 2006. The effect of N rate on grain yield was significant in 2003, 2004, and 2005, but not in 2006. Grain yield and N recovery efficiency (RE) with preplant PCU was greater in 2004 and 2005, and similar in 2003 and 2006 compared with preplant AS or urea. Preplant PCU had similar or greater yield and RE compared with split‐applied AS in 3 yr, but lower yield and RE in the year with the greatest early season rainfall. Nitrification inhibitor (dicyandiamide) showed little impact on corn yield. These results indicated that PCU, when applied preplant, was agronomically and environmentally advantageous over the other N fertilizer sources and typically performed as well as split application of other N fertilizers. However, under conditions where there is a lot of early season rainfall, use of preplant PCU would still result in N losses and then crops would need supplemental N to achieve high yields.